2022
DOI: 10.3390/cells11071094
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Dampens Acute Pulmonary Inflammation via the Adenosine Receptor A2B and Heme Oxygenase-1

Abstract: Acute respiratory distress syndrome is a life-threatening disease associated with high mortality. The adenosine receptor A2B (Adora2b) provides anti-inflammatory effects, which are also associated with the intracellular enzyme heme oxygenase-1 (HO-1). Our study determined the mechanism of sevoflurane’s protective properties and investigated the link between sevoflurane and the impact of a functional Adora2b via HO-1 modulation during lipopolysaccharide (LPS)-induced lung injury. We examined the LPS-induced inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…HO-1 breaks down heme into nitric oxide, biliverdin, and iron to provide an effective antioxidant defense against cellular stress, which is related to ferroptosis [ 20 ]. Pre-and post-conditioning with sevoflurane might protect against ALI by upregulating HO-1 expression [ 21 , 22 ]. Taken together, these results showed that ferroptosis contributes to the prognosis of ALI, and sevoflurane inhibits ferroptosis by upregulating HO-1 expression to ameliorate LPS-induced ALI, which provides novel insights for the clinical application of sevoflurane in ALI therapy.…”
Section: Respiratory Systemmentioning
confidence: 99%
“…HO-1 breaks down heme into nitric oxide, biliverdin, and iron to provide an effective antioxidant defense against cellular stress, which is related to ferroptosis [ 20 ]. Pre-and post-conditioning with sevoflurane might protect against ALI by upregulating HO-1 expression [ 21 , 22 ]. Taken together, these results showed that ferroptosis contributes to the prognosis of ALI, and sevoflurane inhibits ferroptosis by upregulating HO-1 expression to ameliorate LPS-induced ALI, which provides novel insights for the clinical application of sevoflurane in ALI therapy.…”
Section: Respiratory Systemmentioning
confidence: 99%
“…Sevoflurane reduced LPS-induced polymorphonuclear neutrophil (PMN) infiltration and edema in WT mice. Chimeric mice expressing A 2B ARs exclusively on leukocytes showed decreased PMN counts after sevoflurane treatment [ 158 ]. Recent research demonstrated that A 2B AR activation by adenosine is the mechanism by which cupping, a traditional Chinese alternative therapy, attenuates LPS-induced lung inflammation [ 159 ].…”
Section: Ars In Inflammation and Autoimmunitymentioning
confidence: 99%